THE APPLICATION OF EDMODO TO IMPROVE WRITING SKILL - Swara, Marrieta Moddies; Nurjanah, Siti Ulfah (JIPIS, 2021)
The purpose of this experimental study is to investigate the effect of using Edmodo to improve English writing skill by using Edmodo and Traditional method. This experiment was implemented to the senior high school students with two classes, two hours per week, over 3 meetings. Seventy two students participated in this study, with 36 students in the experimental class and 36 others in the control class. The researcher applied pretest and posttest in writing skill with quasi-experimental design. The experimental class was treated learning used Emodo method, whereas the control class received learning used traditional method. The data was analyzed by means, standard deviations, and man u Whitney. Statistical results revealed that the experimental group did much better than the control class. But, in using Edmodo on learning English language there is no significant effect to the class which was treated using Edmodo on improving writing skill at the tenth grade students of SMAN 13 Kabupaten Tangerang. Keywords: application, Edmodo, writing skill